The influence of thermoplastic zein (PEG, GLY and Zein) in bio composite PCL/TZ and HAp via solid state Supercritical CO₂ foaming: article - Nor Wahid, Farrah Khalidah; Subuki, Istikamah (2019)
This research is to study the characterization of the blended poly (ɛ-caprolactone) (PCL), hydroxyapatite (HA) and thermoplastic zein, (thermoplastic zein developed by mixing zein with glycerol (GLY) and poly (ethylene glycol) (PEG)) to form biodegradable porous structure and achieved via the solid state supercritical carbon dioxide (scCO₂) foaming technology. Characterization of the zein which is hydrophobic has been improved by mixing GLY and PEG to increase strength of zein contrast with the mixing of GLY and zein only which lead to a brittle structure. The plasticizers should have polar functional groups for effective zein plasticization, and a proper balance between polar and non-polar functional groups which important for plasticization efficiency. In this research area, this work reported on novel thermoplastic zein by mixing zein with (GLY and PEG) which might be a better way to synergistically improve the properties of natural polymer for foaming application. Thus, the effect of biocomposite material consist of PCL/HAp and TZ with different composition are investigated to generate porous structure via supercritical CO₂. In this work, reported the process of foaming with CO₂ take place for 6h at 50˚C and pressure about 20MPa with high depressurization rate. Foams were characterized by scanning electron microscopy. Result indicated that after saturation of the polymer material with CO₂, high depressurization causes the thermodynamic instability and results in the formation of nucleated gas cells that give rise to pores within the scaffold. The blended composition of PCL₆₀/TZ₂₀/HAp₂₀ show result of well interconnected porous structure compared to other bio composite material prepared. Overall results show foaming effect produce foams with heterogeneous morphologies on bio composite material at relatively low temperature.